Bioinspired hydrophobic surfaces: An overview. (2022) - Bains, Navdeep Singh; Vaishya, Rahul O.; Kant, Suman; Gupta, Anurag
Abstract: Researchers have been trying for years to recreate mother-nature by introducing superhydrophobic qualities into a range of material surfaces, causing them to be non-wetting. A wide range of applications have been observed in space and aerospace, biomedical applications, automotive, engineering, military, apparels, sensors, and other areas. Super hydrophobicity of any surface is that property by which material have tendency to repel water or any other fluid easily. In this article, we will discuss about hydrophobicity and deeply understand about the nature inspired structures, as how their biological structures show fluid repellency and other properties.